Effect of guar gum on the physicochemical, thermal, rheological and textural properties of green edam cheese - Oliveira, N. M. (2011)
In attempts to produce a low-fat cheese with a rheology and texture similar to that of a full-fat cheese, guar gum (within 0.0025–0.01%; w/v, final concentration) was added to low-fat milk. The obtained cheeses were characterised regarding their physicochemical, thermal, rheological and textural properties. Control cheeses were also produced with low and full-fat milk. The physicochemical properties of the guar gum modified cheeses were similar to those of the low-fat control. No significant differences were detected in the thermal properties (concerning the enthalpy and profile of water desorption) among all types of cheeses. The rheological behaviour of the 0.0025% modified cheese was very similar to the full-fat control. Overall, no trend was observed in the texture profile (hardness, cohesiveness, gumminess and elasticity) of the modified cheeses versus guar gum concentration, as well as in comparison with the control groups, suggesting that none of the studied polysaccharide concentrations simulated the textural functions of fat in Edam cheese.